Magnesium Sulphate for Fetal Neuroprotection at Imminent Risk for Preterm Delivery: A Systematic Review With Meta-analysis and Trial Sequential Analysis. Issue 3 (March 2021) - Wolf, H. T.; Huusom, L. D.; Henriksen, T. B.; Hegaard, H. K.; Brok, J.; Pinborg, A.
Abstract : (Abstracted from BJOG 2020;127:1180–1188) Preterm delivery puts infants at risk of developing cerebral palsy (CP). Conventional meta-analyses have shown that administering magnesium sulfate (MgSO4 ) at imminent preterm birth may help decrease this risk.